Calcifying cystic odontogenic tumour associated with odontoma involving mixed dentition - Mandú, Angélica; Gonzaga, Amanda Katarinny; Lopes, Maria Luiza; Nóbrega, Luciana Eloísa; Costa, Antonio (Brazilian Dental Science, 2016)
The calcifying cystic odontogenic tumor (CCOT) is a benign cystic odontogenic tumor relatively uncommon and may be associated with other odontogenic lesions. This manuscript describes a case of CCOT associated with odontoma in a 9-year-old girl, who presented with a slight swelling along with prolonged retention of a maxillary primary central incisor. Radiographic examination showed a unilocular radiolucent lesion containing radiopaque material, associated with an unerupted tooth. Taking into consideration the clinical diagnostic of odontoma, an excisional biopsy was carried out. Microscopic examination established the diagnosis of a CCOT associated with odontoma. The association of these lesions is rare in individuals in the first decade of life, particularly involving mixed dentition, as outlined in this case. The patient remains under care with no clinical signs of recurrence.